Evaluation of enzymatic activity and identification of potent proteolytic and chitinolytic bacteria isolated from crab shell waste - MOH DLIYAUDDIN; TRI ARDYATI; SUHARJONO (Society for Indonesian Biodiversity, 2020)
Abstract. Dliyauddin M, Ardyati T, Suharjono. 2020. Evaluation of enzymatic activity and Identification of Potent Proteolytic and Chitinolytic Bacteria Isolated from Crab Shell Waste. Biodiversitas 21: 211-218. Proteolytic and chitinolytic bacteria are needed to degrade protein-chitin fibers in crab shell waste. These bacteria are important for enhancing the degradation rate of crab shell waste in the environment. This study aims to study the enzymatic activity and identify potent proteolytic and chitinolytic bacteria based on 16S rDNA sequences. The bacteria were isolated from crab shell waste using skim milk agar and colloidal chitin agar for proteolytic and chitinolytic bacteria, respectively. The bacterial isolates were screened based on their protease and chitinase activity using casein and chitin as substrates, respectively. The selected isolates were identified based on 16S rDNA sequences similarity. A total of 20 proteolytic and 22 chitinolytic bacteria were successfully isolated from the samples. The isolate of AP9, AP5, and BP14 had a high protease activity. However, only BP14 and CK20 showed a high chitinase activity. The isolate of AP9 was identified as Bacillus subtilis, AP5, and CK20 were identified as Bacillus licheniformis, and BP14 was identified as Bacillus cereus. AP5 dan CK20 were classified as non-pathogenic isolates.